CLINICAL AND LABORATORY SIGNIFICANCE OF SYSTEMIC INFLAMMATORY MARKERS IN VARIOUS FORMS OF BRUCELLOSIS AND OPTIMIZATION OF TREATMENT - Oblokulov A.R.; Tokhirov F.F (TADQIQOTLAR, 2025)
Abstract Brucellosis remains a significant zoonotic infection worldwide, characterized by a wide spectrum of clinical manifestations and a tendency toward chronicity. Systemic inflammatory response plays a key role in the pathogenesis and clinical course of the disease.  This  article  analyzes  the  clinical  and  laboratory  significance  of  systemic inflammatory  markers  in  different  clinical  forms  of  brucellosis  and  discusses approaches to optimizing treatment strategies based on these markers. Assessment of inflammatory biomarkers allows for improved early diagnosis, evaluation of disease severity, monitoring of therapeutic effectiveness, and prevention of complications.